Índice de proporcionalidade de cobertura: um fator para previsibilidade das características da qualidade nos tecidos de malha - Stein, Vandré (2013)
The jersey fabric, mostly those are compounded of a cotton percentage, they present some characteristics, such as humidity absorption, flexibility and soft surface. These characteristics have their origins in the knitting production sector in the production process. However, the contrast with these properties, one of the main problems with the clothes made with these jersey fabrics is the dimensional instability. This Problem is today one of the biggest threat on the increase about the cotton fabric using to the manufactory of external clothes. The literature shows us a metric, known as covering factor (CF) which is the result of matching between the two fundamental varieties in the knitting: the yarn title and the sewing length. The studies observed in this research shows its importance, however, the application is just in the basic jersey fabric products or they show its concept in the research made over the fabric dimensional instability. In this context, this presentation has the objective to show the study of the application on a new covering factor calculus standard to predict the jersey fabric quality characteristics. This pattern has the objective of helping in the approving or reproving decision about the jersey fabric developments, correlating this factor with the quality characteristics like the width, length, thickness, weight by area, sewing density, resistance, and elasticity. This way was made a study about to correct and enhance this calculus. In the bibliographic revision it was checked all the varieties that had influence in the physic/mechanic process in the manufacturing of the many jersey fabric structures as were analyzed the most important studies as which ones this covering factor was applied. A diagnostic inventory was made in many companies and showed that the currently situation about knowledge application and necessity of the covering factor in the jersey fabric development process. After checking the aspects about the CF comparing the field researches and bibliographic, a solution was searched to reduce the high level failing indexes and the new products delays. In This way a new calculus was conceived for the knitting covering factor based on the Grosberg´s covering factor. After this, was elaborated a computer tool applied on an electronic table where the entire calculus is done automatically after input the necessary data. After this, was elaborated a calculus comparative study between the CF and the proportion covering index (PCI) to test the operability and the functionality of the model and the tool proposed. All the participants answered a quiz referring to the perceptions about the model and the tool. Finally, PCI validity occurred about the analyzes from some jersey fabrics with the objective of investigating if the results generated on the calculus reflected the reality of the quality results obtained at the company. The result of this study indicated that the model of the calculus proposed showed a bigger liability, representatively, and accuracy in the developing of the new jersey fabrics. With this we can confirm that the objectives of this dissertation were reached and positives.